2019
DOI: 10.1002/cbin.11047
|View full text |Cite
|
Sign up to set email alerts
|

miR‐182‐5p overexpression inhibits chondrogenesis by down‐regulating PTHLH

Abstract: miR-182-5p may play a negative role in chondrogenesis by down-regulating PTHLH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…In the present study, to explore the pivotal anti‐inflammatory mechanism of miR‐182, an animal model of ALI was induced by the administration of LPS. We found that miR‐182 decreased in the lung of mice with ALI, which was content with previous results (Bai, Yin, Zhao, Li, & Wu, 2019). And the result of HE staining, MPO, D/W ratio, BALF and proinflammatory cytokines were proved successful establishment of an ALI model.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, to explore the pivotal anti‐inflammatory mechanism of miR‐182, an animal model of ALI was induced by the administration of LPS. We found that miR‐182 decreased in the lung of mice with ALI, which was content with previous results (Bai, Yin, Zhao, Li, & Wu, 2019). And the result of HE staining, MPO, D/W ratio, BALF and proinflammatory cytokines were proved successful establishment of an ALI model.…”
Section: Discussionsupporting
confidence: 92%
“…Several miRNAs can regulate the development of IVDD [26][27][28] . Although miR-182-5p has been associated with a variety of human diseases 29,30 , this is the first study to identify miR-182-5p as a key factor in IVDD. We found that miR-182-5p could promote apoptosis and reduce mitophagy, and these effects were related to the regulation of circERCC2 on miR-182-5p/SIRT1 axis.…”
Section: Discussionmentioning
confidence: 90%
“…MiR-92a-3p may be involved in regulating cartilage development by targeting WNT5A (Mao et al, 2018b). Conversely, miR-182-5p plays a negative role in BM-MSC chondrogenesis by downregulating parathyroid hormone-like hormone (PTHLH) (Bai et al, 2019). Table 1 summarizes the miRNAs, related to cartilage development, that have been studied in recent years.…”
Section: Cartilagementioning
confidence: 99%